Mulher, gênero e organização política no Assentamento Oziel – MST: Porto Franco-MA - Morais, Alessandra da Conceição (Universidade Federal do Tocantins, 2021)
The present work aims to present the theme Woman, gender and political organization in the MST: once the land is conquered, how does the organization and division of tasks between women and men occur, with the objective of understanding the position on the issue of seated woman and the places occupied by them. Understand how the organization and the gender relationship takes place from the interview that took place with the residents of this community, which has a representation within the settlement based on housing construction, health needs, and the organization of the entry of new residents, etc. The research starts from an analysis of the participation of women in the struggle for territory, highlighting their role in the process of struggles and conquests of the Oziel Settlement. It seeks to understand whether the divisions of labor and organization of the settlement differ in relation to gender, that is, whether men have more participation and opportunities than women. The methodology used a qualitative approach with field research and interview script. The results obtained in the research showed us that the Oziel Alves settlement has become a settlement with a good infrastructure, with the division of labor occurring individually for each family, but within each one of them women are present both in the home as in the farm service.